The Impact of Ethnomathematics Activities Using Zapin and Kuda Kepang Dances on Students' Academic Achievement and Appreciation of Isometric Transformations - Abdullah, Abdul Halim; Zakaria, Mohamad Ikram; Mokhtar, Mahani; Khairuddin, Nur Khairina; Mohamad Rasol, Nur Izzah Atirah; Hanafi, Nurul Hazreen; Suhaimee, Nurul Rabiatul Adawiyah; Syahri, Indawan; Antoni; Apriana; Rini Susanti; Yuliarni (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Cultural integration in education has emerged as a powerful tool for enhancing student engagement and learning outcomes. However, the specific impact of cultural integration on mathematics education, particularly in relation to students' academic achievement and their appreciation of mathematical beauty, has not been thoroughly examined. This study explores the effects of a teaching module that integrates Zapin and Kuda Kepang dances with isometric transformations on these outcomes. Using a quasi-experimental design, the research involved 60 Form Two students from Johor Bahru, divided into treatment and control groups. The module was implemented over five weeks, with data collected through academic performance tests, questionnaires, and semi-structured interviews. Independent t-tests and Mann-Whitney U tests (conducted using SPSS version 21) revealed significant improvements in academic achievement and appreciation of mathematical beauty among students in the treatment group. Thematic analysis of interview data further revealed increased motivation, interest, and emotional connection to mathematics. These findings highlight the potential of integrating cultural elements into mathematics education to foster deeper engagement and academic success, emphasizing the need for innovative teaching approaches in secondary education.